Genetic transformation in Staphylococcus aureus: isolation and characterization of a competence-conferring factor from bacteriophage 80 alpha lysates. - Birmingham, V A (1981)
The competence-conferring activity in crude lysates of the staphylococcal bacteriophage 80 alpha was concentrated and purified by (NH4)2SO4 precipitation, differential ultracentrifugation and rate-zonal centrifugation through Ficoll. This concentrated preparation exhibited lytic activity toward assay cells of Staphylococcus aureus 8325-4 that could not be attributed to the residual 80 alpha infectious particles present. Electron microscopic examination of the concentrated competence-conferring activity revealed an occasional intact but empty virion and large numbers of free phage tails. Sodium dodecyl sulfate-polyacrylamide gel analysis of this material confirmed that the competence-conferring activity contained only some, but not all, of the major virion proteins. The competence-conferring activity exhibited single-hit kinetics when assay cells and 80 alpha transfecting deoxyribonucleic acid were present in excess. The competence-conferring activity thus seems to be a unique morphogenic precursor of the 80 alpha virion that mediates transfection and transformation in the presence of 0.1 M CaCl2.